2001
DOI: 10.1080/14733140112331385268
|View full text |Cite
|
Sign up to set email alerts
|

Moments of empowerment: A qualitative analysis of positively experienced episodes in brief person‐centred counselling

Abstract: 38 positively experienced episodes in brief person‐centred counselling with six clients were analysed. The Interpersonal Process Recall (IPR) method was used as the prime research tool. Clients were asked to identify positively experienced moments in the counselling session during a post‐session review interview. Clients and counsellors were invited to report on the feelings, perceptions and intentions they recalled experiencing during these moments. Three analyses were used to categorise the meaning and feeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 17 publications
0
17
0
3
Order By: Relevance
“…For anxiety problems (especially panic and generalized anxiety), Elliott et al (2013) reported large pre-post effects, moderate controlled effects, but consistently poorer results when compared to CBT. Although researcher allegiance effects are a factor, Elliott et al (2013) argued that more work is required to develop more effective process-guiding approaches, as indicated by evidence now emerging from ongoing research (Timulak & McElvaney, 2012). At this point, however, based on the available evidence, the use of traditional humanistic therapies can only be justified as second-line treatments for clients who have also tried or refused CBT.…”
Section: (11)mentioning
confidence: 94%
“…For anxiety problems (especially panic and generalized anxiety), Elliott et al (2013) reported large pre-post effects, moderate controlled effects, but consistently poorer results when compared to CBT. Although researcher allegiance effects are a factor, Elliott et al (2013) argued that more work is required to develop more effective process-guiding approaches, as indicated by evidence now emerging from ongoing research (Timulak & McElvaney, 2012). At this point, however, based on the available evidence, the use of traditional humanistic therapies can only be justified as second-line treatments for clients who have also tried or refused CBT.…”
Section: (11)mentioning
confidence: 94%
“…We then reduced our selection to seven studies (see Table 1) as three of the studies (Timulak, Belicova, & Miler, 2010;Timulak & Elliott, 2003;Timulak & Lietaer, 2001) had a broader focus than insight events, such as empowerment events, and their description of the processes in insight events offered only very abstract and very general perspectives. Although the initial analysis was conducted on all ten studies, we observed that while these three studies did not contradict findings from other studies, they were not sufficiently detailed to contribute beyond the remaining seven studies.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…The IPR has been used in a number of studies on psychotherapy process examining a range of questions (Frankel & Levitt, 2009;Levitt & Piazza-Bonin, 2011;Rice & Greenberg, 1984;Timulák & Lietaer, 2001). In its more structured form, participants are asked to respond to rating scales measuring the constructs of interest (Wiseman & Rice, 1989).…”
mentioning
confidence: 99%